Conceptualization of digitalization - Gorenšek, Tilen (International journal of Euro-Mediterranean studies, 2019)
Digitalization is radically interfering and changing the fundamental assumptions of the way of life and organization of work in a postmodern society, which is becoming more globalized and more digitalized than ever before. Therefore it is becoming increasingly important for organizations to quickly, efficiently, and appropriately plan the digital transformation to achieve flexibility and to maintain market competitiveness. In this context, the understanding of digitalization and related concepts is vital. The paper focuses on the social and organizational level and highlights the conceptualization of digitalization and the results of previous research, which support the hypotheses of significant organizational changes while highlighting the opportunities and challenges that digitalization brings to society and organizations in the Euro-Mediterranean area and around the world.
Keywords: Digitalizacija; Digitization; Organizacijske spremembe; Organizational change; Organizational sociology; Sociologija organizacije